ENDPLATE DEFLECTION IS A DEFINING FEATURE OF VERTEBRAL FRACTURE AND IS ASSOCIATED WITH PROPERTIES OF THE UNDERLYING TRABECULAR BONE - Jackman, Timothy M (J Orthop Res, 2014)
Endplate deflection frequently occurs with vertebral failure, but the relationship between the two remains poorly defined. This study examined associations between endplate deflection under compressive loading and characteristics of the neighboring subchondral bone and intervertebral disc (IVD). Ten L1 vertebrae with adjacent IVDs were dissected, compressed axially in a stepwise manner to failure, and imaged with micro-computed tomography before each loading step. From the images, deflection was measured across the surface of each endplate at each step. Trabecular microstructure and endplate volume fraction were evaluated in 5mm regions just under the superior endplate. IVDs were assessed using computed tomography and histology. A marked increase in superior endplate deflection coincided with a drop in the load-displacement curve. Endplate deflection was higher in regions with less robust bone microstructure (p<0.009), though these associations tended to weaken as loading progressed. Immediately following the ultimate point, endplate deflection was higher in regions underlying the nucleus pulposus vs. annulus fibrosus (p=0.035), irrespective of disc grade (p=0.346). These results indicate that a sudden increase in endplate deflection signals that the mechanical competence of the vertebra has been compromised. The mechanisms of endplate failure likely relate to anatomical features of the endplate, neighboring trabecular bone, and IVD.